Epidemiology of Dandy-Walker Malformation in Europe: A EUROCAT Population-Based Registry Study - Santoro, Michele (2020)
Background: Dandy-Walker (DW) malformation is a rare and severe congenital anomaly of the posterior fossa affecting the development of the cerebellum and the fourth ventricle. Objective: The aim of this study was to investigate the epidemiology of DW malformation, using data from the European population-based registries of congenital anomalies in the European Surveillance of Congenital Anomalies network. Methods: Anonymous individual data on cases of DW malformation diagnosed in 2002-2015 from 28 registries in 17 countries were included. Prevalence, prenatal detection rate, proportions and types of associated anomalies were estimated. Cases of DW variant were considered and analysed separately. Results: Out of 8,028,454 surveyed births we identified a total of 734 cases, including 562 DW malformation cases and 172 DW variant cases. The overall prevalence of DW malformation was 6.79 per 100,000 births (95% CI 5.79-7.96) with 39.2% livebirths, 4.3% foetal deaths from 20 weeks gestational age, and 56.5% terminations of pregnancy after prenatal diagnosis of foetal anomaly at any gestation (TOPFA). The livebirth prevalence was 2.74 per 100,000 births (95% CI 2.08-3.61). The prenatal detection rate was 87.6%. Two-hundred and seventy-three cases (48.6%) had an isolated cerebral anomaly and 24.2, 19.2 and 5.5% cases were associated with other structural non-cerebral anomalies, chromosomal anomalies and genetic syndromes respectively. The prevalence of DW variant was 2.08 per 100,000 (95% CI 1.39-3.13). Conclusions: This European population-based study provides the epidemiological profile of DW malformation. All birth outcomes were analysed and TOPFA represented more than half of the cases. About 50% of the cases of DW malformation were associated with other non-cerebral anomalies. Large populations and all birth outcomes are essential in epidemiological studies of rare and severe congenital anomalies.